Specific sulfation and glycosylation—a structural combination for the anticoagulation of marine carbohydrates - Pomin, Vitor H.; Mourão, Paulo A. (Frontiers in Cellular and Infection Microbiology, 2014)
Based on considered achievements of the last 25 years, specific combinations of sulfation patterns and glycosylation types have been proved to be key structural players for the anticoagulant activity of certain marine glycans. These conclusions were obtained from comparative and systematic analyses on the structure-anticoagulation relationships of chemically well-defined sulfated polysaccharides of marine invertebrates and red algae. These sulfated polysaccharides are known as sulfated fucans (SFs), sulfated galactans (SGs) and glycosaminoglycans (GAGs). The structural combinations necessary for the anticoagulant activities are the 2-sulfation in α-L-SGs, the 2,4-di-sulfation in α-L-fucopyranosyl units found as composing units of certain sea-urchin and sea-cucumber linear SFs, or as branching units of the fucosylated chondroitin sulfate, a unique GAG from sea-cucumbers. Another unique GAG type from marine organisms is the dermatan sulfate isolated from ascidians. The high levels of 4-sulfation at the galactosamine units combined with certain levels of 2-sulfation at the iduronic acid units is the anticoagulant structural requirements of these GAGs. When the backbones of red algal SGs are homogeneous, the anticoagulation is proportionally dependent of their sulfation content. Finally, 4-sulfation was observed to be the structural motif required to enhance the inhibition of thrombin via heparin cofactor-II by invertebrate SFs.